Budget Planning Strategy, Revenue And Control Of Non-Revenue Water (NRW) On Financial Performance Through SOP (Standard Operating Procedure) As An Intervening Variable At Perumda Air Minum Tirta Raharja Bandung - Hari Sundana; Supardi Supardi; Hadiah Fitriyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of Budget Planning Strategy, Revenue, and Unbilled Water (ATR) Control on Financial Performance at Perumda Air Minum Tirta Raharja Bandung, with Standard Operating Procedure (SOP) as an intervening variable. The research is based on the importance of operational efficiency and corporate governance in regional water utility companies, particularly in facing financial and technical challenges related to budgeting, revenue optimization, and the control of non-revenue water (ATR). SOP plays a vital role as a system that standardizes operational procedures, ensuring that activities are performed efficiently and contribute to improved financial performance. This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The sample consists of 150 respondents, comprising operational and managerial employees at Perumda Air Minum Tirta Raharja, who are directly involved in budgeting, revenue management, ATR control, and SOP implementation. Data were collected through structured questionnaires using a 5-point Likert scale. The analysis was conducted using SmartPLS software to test the measurement model (outer model), structural model (inner model), and the mediating effect of SOP. The results show that Budget Planning Strategy, Revenue, and ATR Control have a positive and significant effect on SOP. Furthermore, SOP has a positive and significant effect on Financial Performance. In addition, SOP partially mediates the relationship between the three independent variables and Financial Performance. This indicates that better budgeting strategies, effective revenue management, and optimal ATR control, combined with well-implemented SOPs, contribute significantly to improved financial performance.